ANALISIS PENGARUH CAR, NIM, NPL, DAN LDR TERHADAP ROA (Studi Kasus pada Bank Umum Persero BUMN Periode 2013-2018) - Amir Triyadi Sanjoyo (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2020)
Banks must carry out their activities with the precautionary principle so as not to harm the wider community such as the banking crisis of 1998 and 2008, therefore Bank Indonesia issued regulation no. 13/1 / PBI / 2011 in 2012 as a guideline for banks to maintain banking health using the RGEC method. This research was conducted to determine the effect of the CAR, NIM, NPL, and LDR ratio to the ROA ratio. With all of the above ratios are from the Bank Indonesia RGEC assessment method, on BUMN banks consisting of BNI, Mandiri, BRI, and BTN. This study uses multiple linear regression analysis using SPSS 21 application with a six-year observation period (2013-2018) from four state-owned banks with independent variables CAR (X1), NIM (X2), NPL (X3) and LDR (X4) and variables dependent on ROA (Y). The results of this study shows that simultaneously CAR, NIM, NPL, and LDR ratios have a significant effect on ROA, while partialy each of the ratio CAR has a significant and negative effect on ROA, NIM has a positive and significant effect on ROA, and NPL has a significant and negative effect on ROA while LDR ratio does not significantly influence ROA. So the researcher's suggestion is that the capital in CAR can be channeled back into the productive assets to increase bank profits both in terms of interest (NIM) and overall profit (ROA) while the NPL ratio can be improved risk management so as not reduce bank profits both NIM and ROA and for the LDR ratio so that Bank BTN adjusts its LDR ratio in accordance with Bank Indonesia regulations.